PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PENGGUNA PERPUSTAKAAN (DI POLITEKNIK NEGERI BATAM) - Gunartik Gunartik; Nora Pitri Nainggolan (LPPM Universitas Putera Batam, 2019)
The library is a place that becomes a service provider that contains information. Independent variables in this study are service quality and facilities, the dependent variable is library user satisfaction. This study aims to study the quality of services and facilities for library user satisfaction. by using primary data and secondary data, data collection techniques by distributing questionnaires. The population in this study were students using the Business Administration (AB) library in 2018 in the last three months, namely July, August, September as many as 3208 people. The sample in this study amounted to 100 taken using probability sampling techniques with random sampling method. The results of the study stated that valid and reliable, normal, did not occur Multicollinearity and Heteroscedasticity. The results of the F Test show that the quality of service and facilities have a positive and significant effect on the satisfaction of library users. the results of the T Test show that the value of service quality has a positive and significant effect on user satisfaction. while facilities have a positive and significant effect on user satisfaction.